Knowledge, Family Support And Role Of Friends Of People In The Attitude Of Traffickers In Following The Rehabilitation Program In IPWL Bambu Nusantara Foundation Of Madiun City - Tri Hari Wahyuningtyas; Nurwijayanti Nurwijayanti; Ratna Wardani; Diyah Herowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The rise of illegal drugs such as narcotics, can affect adolescents. If teenagers already use drugs, it is certainly very dangerous because it can affect their mentality and personality. The purpose of this study was to analyze knowledge, family support and the role of peers in the attitude of drug users in participating in the rehabilitation program at the IPWL of the Bambu Nusantara Foundation in Madiun City. The design of this study was an observational quantitative study with a cross section approach with the focus of the research directed to be to analyze knowledge, family support and the role of peers in the attitude of drug users in participating in the rehabilitation program at the Bambu Nusantara Foundation IPWL in Madiun City with a population of 160 respondents and 114 samples respondents taken with the Simple Random Sampling technique. The findings found that almost half of respondents had medium category knowledge of 56 respondents (49.1%). Nearly half of the respondents had sufficient family support as many as 48 respondents (42.1%). Nearly half of the respondents had the role of peer categories as many as 49 respondents (43%). Nearly half of respondents have the attitude of the sufficient category as many as 51 respondents (44.7%). The results of the study using the Multiple Linear Regression Test showed that the p-value <0.05 then H0 was rejected so it was concluded that there was an influence of knowledge, family support and the role of peers on the attitude of drug users in participating in the rehabilitation program at the IPWL of the Bambu Nusantara Foundation in Madiun City. Knowledge about drugs is very important to be given early to anyone in order to understand more deeply about the risks and impacts of drug consumption. In this case the family is very important to monitor the association of family members so as not to fall into the wrong association with their peers